Suara Di Balik Larik: Analisis Naratif Pengalaman Estetis Dan Katarsis Emosi Siswa Kelas Vii Smp Pluss Ja'al Haqq Kota Bengkulu Dalam Menulis Puisi Bebas - Rinanda Puppri, Karista; Salamah; Putri Juni Astuti, Dina (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to conduct an in-depth investigation of the aesthetic experiences and emotional catharsis processes experienced by seventh-grade students at SMP Pluss Ja'al Haqq in Bengkulu City through free-form poetry writing activities. Using a qualitative approach with narrative analysis, this study explores the personal stories, reflections, and poetry manuscripts produced by the students as forms of psychological articulation. Data were collected through in-depth narrative interviews with eight key informants, participatory observation during the literature learning process, and documentation in the form of student poetry portfolios. Data validity was tested through triangulation of sources and techniques. The data analysis process followed Labov and Waletzky’s narrative model, integrated with Aristotle’s theory of catharsis and the aesthetics of taxation. The research findings indicate that writing free-verse poetry serves as a safe space for students in early adolescence to voice inner conflicts, academic anxiety, peer pressure, and family dynamics. Students experience aesthetic engagement through the process of contemplation, the selection of diction that transcends literal meaning, and the discovery of metaphors that represent their emotional states. Emotional catharsis manifests itself in the form of a sense of relief, a reduction in psychological burden, and increased self-awareness after negative emotions have been successfully channeled into lines of poetry. This study concludes that literature education, particularly the writing of free verse poetry, possesses a crucial sociopsychological therapeutic dimension; therefore, the reorientation of literary pedagogy should be directed toward an expressive-humanistic approach, rather than merely evaluating mechanistic-linguistic aspects.